Diversity of wild edible plants, nutrition and phytochemical evaluation of certain plants with ethnobotanical importance from Tinsukia district, Assam, India - Pankaj , Saikia; Daimalu, Baro; Amal , Bawri; Biswadeep , Doley; Sanjay , Basumatary; Nipen , Nayak; Arjun, Adhikari (Plant Science Today, 2025)
The present study was conducted in 2021-2023 and recorded a total of 96 species, out of which 56 % were used as vegetables, 30 % as edible fruits and 7 % as masticatory, spice and condiments. This study also aims to evaluate the nutritionally important minerals concentration and phytochemical constituents of 5 plant taxa, i.e., Sarcochlamys pulcherrima (Roxb.) Gaud., Zanthoxylum oxyphyllum Edgew., Smilax perfoliata Lour., Portulaca oleracea L. and Phlogacanthas thyrsiformis (Hardw.) Mabb. which are widely used in folk healing practices and folk medicine by the various ethnic communities of Tinsukia district. The concentration of 5 macro minerals Na, K, Ca, Mg and P is in the range of 12.5 -18.4, 90.4 -246.9, 140 -214.3, 84.9 - 112.2, 23.7 - 41.2 mg/100 g respectively. The ratio of K/Na (5.9:1 to13.4:1), Ca/P (4.1:1 to 9.1:1) and K/(Ca+Mg) (0.11:1 to 0.32:1) are found to be adequate ratios ranging from respectively. Microminerals like Fe, Zn, Cu, Mn and Ni are found in the range between 5.90 -16.17, 0.41-0.91, 0.13 -0.32, 0.07 -0.27 and 0.07 - 0.17 mg/100 g respectively. Some of the important phytochemicals are also found to be present in the analyzed plants. The study shows that consumption of these species may be beneficial for maintaining good mineral nutrition among the common people at a minimum cost.